2019
DOI: 10.1007/s10714-019-2606-2
|View full text |Cite
|
Sign up to set email alerts
|

Topological and noninertial effects in an Aharonov–Bohm ring

Abstract: In this paper, we study the influence of topological and noninertial effects on a Dirac particle confined in an Aharonov-Bohm (AB) ring. Next, we explicitly determine the Dirac spinor and the energy spectrum for the relativistic bound states. We observe that this spectrum depends on the quantum number n, magnetic flux Φ of the ring, angular velocity ω associated to the noninertial effects of a rotating frame, and on the deficit angle η associated to the topological effects of a cosmic string. We verified that … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 95 publications
0
8
0
Order By: Relevance
“…Based on nonrelativistic wave equations, several studies have shown the influence of linear topological defects on the electronic properties of solids [41][42][43][44][45][46][47][48]. Linear topological defects have also been studied in quantum rings [49][50][51][52], for an electron subject to the deformed Kratzer potential [53] and subject to a uniform magnetic field [54][55][56][57]. The most promising perspective in the studies of linear topological defects is the appearance of Aharonov-Bohm-type effects [58][59][60][61].…”
Section: Introductionmentioning
confidence: 99%
“…Based on nonrelativistic wave equations, several studies have shown the influence of linear topological defects on the electronic properties of solids [41][42][43][44][45][46][47][48]. Linear topological defects have also been studied in quantum rings [49][50][51][52], for an electron subject to the deformed Kratzer potential [53] and subject to a uniform magnetic field [54][55][56][57]. The most promising perspective in the studies of linear topological defects is the appearance of Aharonov-Bohm-type effects [58][59][60][61].…”
Section: Introductionmentioning
confidence: 99%
“…As a final comment, we would like to emphasize that the model studied in this article generalizes others found in the literature, such as those of Refs. [68,72] for the case including a superposition of external magnetic fields and the investigation of isolated solutions of the Dirac equation. Furthermore, we present a detailed discussion on the energy levels of the particle which, in general, is not found in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…This way, it is also an attractive question examining how the electromagnetic interactions affect the particle quantum motion of a rotating system in the presence of a topological defect. Reference [68], for instance, is a recent work dealing with both topological and noninertial effects in the presence of an Aharonov-Bohm potential. Reference [69] addresses the problem of a spinless relativistic particle subjected to a uniform magnetic field in the spinning cosmic string spacetime.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, there still exists a debate on the origin, interpretations and implications of the AB effect [16][17][18][19]. There are also relevant works in the literature on the AB effect applied to other physical systems, for example, problems involving spin and pseudo-spin symmetries [20][21][22][23][24][25][26][27][28], topological defects [29][30][31][32][33][34][35], thermodynamic aspects [36][37][38][39][40][41][42][43], κ-deformed algebra [44,45], Lorentz symmetry violation [46][47][48][49] and Duffin-Kemmer-Petiau (DKP) formalism [50][51][52][53]. Another topic of central importance in this context refers to the description of the AB effect by taking into account the electron spin degree of freedom [54].…”
Section: Introductionmentioning
confidence: 99%